Artificial intelligence in education open learning environments : new computational technologies to support learning, exploration and collaboration - Lajoie, Susanne P.; Lajoie, Susanne P.; Vivet, Martial (Amsterdam ; Washington, DC : IOS Press, 1999)
This text presents the proceedings from the 9th International Conference on Artificial Intelligence, one from a series of conferences designed to report on the state of the art research in the field of artificial intelligence in education.
Understanding Texts and DialoguesVirtual Realities and Virtual Campuses; Posters; Panels; Luncheon Speakers; Workshops; Tutorials; Author Index
Description based upon print version of record.
English
Includes bibliographical references and index.
Keywords: Intelligent tutoring systems -- Congresses; Artificial intelligence -- Educational applications -- Congresses; Open learning -- Congresses